Napoleon for dummies - Markham, J. David. (Wiley Pub. Inc., 2005)
This book is divided into 10 parts, each consisting of 3 to 4 short chapters that focus on a general theme, such as how Napoleon built his empire, how he lost it, why some of his reforms and ideas were so revolutionary, and the impact he had on Europe. Markham also addresses such issues as Napoleon's height, why he was portrayed with his hand in his vest, and whether he really divorced his 47-year-old wife to marry an 18-year-old princess. The author writes as if he were engaged in a conversation with readers rather than as a noted scholar